The examined life: A study of identity formation,agency, self-expression among imprisoned women - Irene C. Baird (Adult Education Research Conference, 1999)
This study demonstrated the efficacy of a Freirian/humanities-based adult education program on identity formation, agency and empowerment through self-expression within the context of a women's group in a county jail.